Job strain among white-collar employees and its effect on consumption - Berişler, Elif (İstanbul Bilgi Üniversitesi, 2019)
[Abstract Not Available]
Beyaz yaka çalışanlarında iş tükenmişliği ve bunun tüketime etkisi